2013
DOI: 10.1371/journal.pone.0065324
|View full text |Cite
|
Sign up to set email alerts
|

To Clone or Not to Clone? Induced Pluripotent Stem Cells Can Be Generated in Bulk Culture

Abstract: Induced pluripotent stem cells (iPSCs) are usually clonally derived. The selection of fully reprogrammed cells generally involves picking of individual colonies with morphology similar to embryonic stem cells (ESCs). Given that fully reprogrammed cells are highly proliferative and escape from cellular senescence, it is conceivable that they outgrow non-pluripotent and partially reprogrammed cells during culture expansion without the need of clonal selection. In this study, we have reprogrammed human dermal fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 50 publications
(62 reference statements)
1
35
0
Order By: Relevance
“…Other groups have also started to perform similar selection by pooling iPS cells derived from human fibroblasts [48,49]. Both studies showed that high-quality iPS cells can be obtained from pooling of bulk cultures and expanded more efficiently than using individual colonies.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have also started to perform similar selection by pooling iPS cells derived from human fibroblasts [48,49]. Both studies showed that high-quality iPS cells can be obtained from pooling of bulk cultures and expanded more efficiently than using individual colonies.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the size limitation for gene transfer using lentivirus (~9–10 kb between LTRs [27]), we had to use a short version (~1.7 kb) of the 3′ end of the classical 6.5 kb-long α-MHC promoter. Although this fragment contained important gene expression regulatory elements (TATA box, MEF-1 MEF-2 and Nkx2.5 binding sites) [34], it is likely that unidentified enhancing elements were not present explaining the weak GFP expression.…”
Section: Discussionmentioning
confidence: 99%
“…This shortening of the repeat was sufficient to restore normal levels of DNA methylation at the locus, allow FMRP expression, and rescued the neural progenitor cells in terms of neurodevelopmental deficits 14 . These observations point to the importance of repeat length in epigenetic silencing of FMRP and highlight the need to consider somatic mosaicism (or repeat instability) along with the need to characterize multiple clones from subjects if single cell clones are selected 16 . Importantly in terms of replication of findings in different FMR1 mutation lines, similar neurodevelopmental deficits have been reported in both human embryonic stem cell (hESC) models 12,13 and in other iPSC models 15 .…”
Section: Phenotypic Assays In Human Ipsc Models Of Neuropsychiatrimentioning
confidence: 97%